Alleviating salinity stress in canola (Brassica napus L.) through exogenous application of salicylic acid - Maria Ilyas; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Kamran Ahmad; Nargis Naz; Muhammad Fraz Ali; Muhammad Ahmad; Qasim Ali; Jean Wan Hong Yong; Hayssam M. Ali (BMC Plant Biology, 2024)
Abstract Canola, a vital oilseed crop, is grown globally for food and biodiesel. With the enormous demand for growing various crops, the utilization of agriculturally marginal lands is emerging as an attractive alternative, including brackish-saline transitional lands. Salinity is a major abiotic stress limiting growth and productivity of most crops, and causing food insecurity. Salicylic acid (SA), a small-molecule phenolic compound, is an essential plant defense phytohormone that promotes immunity against pathogens. Recently, several studies have reported that SA was able to improve plant resilience to withstand high salinity. For this purpose, a pot experiment was carried out to ameliorate the negative effects of sodium chloride (NaCl) on canola plants through foliar application of SA. Two canola varieties Faisal (V1) and Super (V2) were assessed for their growth performance during exposure to high salinity i.e. 0 mM NaCl (control) and 200 mM NaCl. Three levels of SA (0, 10, and 20 mM) were applied through foliar spray. The experimental design used for this study was completely randomized design (CRD) with three replicates. The salt stress reduced the shoot and root fresh weights up to 50.3% and 47% respectively. In addition, foliar chlorophyll a and b contents decreased up to 61–65%. Meanwhile, SA treatment diminished the negative effects of salinity and enhanced the shoot fresh weight (49.5%), root dry weight (70%), chl. a (36%) and chl. b (67%). Plants treated with SA showed an increased levels of both enzymatic i.e. (superoxide dismutase (27%), peroxidase (16%) and catalase (34%)) and non-enzymatic antioxidants i.e. total soluble protein (20%), total soluble sugar (17%), total phenolic (22%) flavonoids (19%), anthocyanin (23%), and endogenous ascorbic acid (23%). Application of SA also increased the levels of osmolytes i.e. glycine betaine (31%) and total free proline (24%). Salinity increased the concentration of Na+ ions and concomitantly decreased the K+ and Ca2+ absorption in canola plants. Overall, the foliar treatments of SA were quite effective in reducing the negative effects of salinity. By comparing both varieties of canola, it was observed that variety V2 (Super) grew better than variety V1 (Faisal). Interestingly, 20 mM foliar application of SA proved to be effective in ameliorating the negative effects of high salinity in canola plants.